2020
DOI: 10.1371/journal.pone.0234184
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a nursing and midwifery exchange between rural and metropolitan hospitals: A mixed methods study

Abstract: Peer Review History: PLOS recognizes the benefits of transparency in the peer review process; therefore, we enable the publication of all of the content of peer review and author responses alongside final, published articles. The editorial history of this article is available here:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, developing appropriate strategies for midwives, particularly in the context of low- and middle-income countries, first requires an understanding of the influencing factors that have been addressed in the present study. For example, exchange programmes for midwives and other health professionals from urban to rural areas and vice versa, a have been introduced in other settings [ 42 , 43 ], may not be a welcome strategy in the present case, as working and personal conditions are so harsh.…”
Section: Discussionmentioning
confidence: 99%
“…However, developing appropriate strategies for midwives, particularly in the context of low- and middle-income countries, first requires an understanding of the influencing factors that have been addressed in the present study. For example, exchange programmes for midwives and other health professionals from urban to rural areas and vice versa, a have been introduced in other settings [ 42 , 43 ], may not be a welcome strategy in the present case, as working and personal conditions are so harsh.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is an element of empowerment, and competence of new graduate nurses is positively associated with empowerment, signifying that new graduate nurses with higher selfefficacy demonstrate greater levels of competence (Numminen et al, 2015). Conversely, job dissatisfaction can cause emotional exhaustion and a lack of self-efficacy, which can precipitate feelings of burnout and cognitive dissonance (Byrne et al, 2020). A qualitative Canadian study by Waddell et al (2015) suggested that self-efficacy can have a significant influence on new graduate nurses' satisfaction with their job and career, as well as turnover.…”
Section: Empirical Literature About Self-efficacymentioning
confidence: 99%
“…Studies have suggested that leadership and management could also be associated with new graduate nurse retention. Support from nurse managers has been noted to help ease new graduate nurses' transition to practice by helping them to navigate their transition to practice, providing support, creating healthy work environments, discouraging negative workplace behaviours, establishing anti-bullying policies, and exhibiting authentic leadership behaviours (Boamah & Laschinger, 2015;Byrne et al, 2020;Fallatah et al, 2017;Flinkman & Salanterä, 2015;. Fallatah et al (2017) indicate that when nurse managers are authentic leaders, they promote new graduate nurses' intention to stay in their position by helping them to identify with their organization and their leader.…”
Section: Supportive Work Environmentsmentioning
confidence: 99%
“…To test validity and understand how representative the framework is of diverse health care interventions and settings, it has been tested within various health care studies. [13][14][15][16][17][18][19] We seek to add to this literature by testing it within this work, with the constructs and domains providing a simple set of evaluation questions that formed the evaluation benchmark (see File 1, Supplemental Digital Content, http://links.lww.com/QAI/B644).…”
Section: Sustainability Definition and Frameworkmentioning
confidence: 99%